Bolivia : Third Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criteria, and Augmentation and Extension of the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Bolivia's Third Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criteria are discussed. The highly dollarized financial system suffered a renewed deposit run in October 2003, and conditions in the financial sector have remained fragile in 2004. Spending exceeded program targets by 0.7 percent of GDP, mostly owing to higher capital expenditure by municipalities, reflecting in part efforts to reduce social tensions. The authorities have allowed interest rates to increase in response to liquidity conditions and have been able to start placing a moderate amount of bonds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet